Heart failure with preserved ejection fraction and obesity: emerging metabolic therapeutic strategies - Wenwen Zheng; Qianxian Qi; Jie Li; Chaojie He; Hongyan Fan (Diabetology & Metabolic Syndrome)
Abstract The global prevalence of obesity is rapidly in creasing, significantly increasing the incidence of heart failure with preserved ejection fraction (HFpEF). Obesity, one of the most common clinical phenotypes of HFpEF, facilitates the onset and progression of HFpEF via multiple pathophysiological mechanisms. Lifestyle intervention, which serves as the cornerstone of weight loss, plays a crucial role in the management of HFpEF. Novel antidiabetic therapies, including sodium glucose cotransporter 2 inhibitors (SGLT2i), glucagon-like peptide-1 receptor agonists (GLP-1 RA), and glucose‒dependent insulinotropic polypeptide (GIP)/glucagon‒like peptide-1 (GLP-1) dual receptor agonists, have favourable effects on clinical outcomes in obese HFpEF patients. For patients with heart failure (HF) prior to bariatric surgery (BSx), there is moderate evidence supporting the efficacy and safety of the procedure. This review systematically summarizes the clinical evidence related to metabolic therapy treatment strategies for obese HFpEF patients and discusses the potential advantages of such therapy.